The Influence of Parental Attachment to Career Maturity with Self Efficacy as Mediator - Qudsiyah, Ummi; Wibowo, Mungin Eddy; Mulawarman, Mulawarman (Jurnal Bimbingan Konseling, 2018)
This study aims to obtain empirical data and ensure the significance between parental attachment and analyze self efficacy as a mediation variable on career maturity. The research design used is correlational research design with a sample of 323 students selected by using sample random sampling technique. Data collection using the Inventory of Parent and Peer Attachment (IPPA) instruments, Career Decision Self Effiacy Scale-Short Form (CDSE-SF), and Career Maturity Scale. The mediator analysis technique uses corrected bootstrap method (N = 5000) with 95% confidential interval in PROCESS software. The results showed that Parental attachment through self efficacy has an influence on career maturity. The conclusion is that parental attachment has a significant indirect effect on career maturity